The dynamic instability of actin filament barbed ends - Romet-Lemonne, Guillaume (J Cell Biol, 2021)
The turnover of actin filament networks in cells has long been considered to reflect the treadmilling behavior of pure actin filaments in vitro, where only the pointed ends depolymerize. Newly discovered molecular mechanisms challenge this notion, as they provide evidence of situations in which growing and depolymerizing barbed ends coexist.